Kecemasan dan Kebiasaan Belajar Matematika Terhadap Keterampilan Berpikir Kritis Siswa - Muhammad Rifqi Al Fifari; Widodo Winarso (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This study aims to examine the anxiety and study habits of mathematics on students' critical thinking skills. This research approach is a quantitative approach to the type of ex post facto research. The population in this study were students of MA Tarbiyatul Muta’alimin Kabupaten Cirebon. The sampling technique in this study uses purposive sampling. As for the research sample of 40 students. Data collection techniques used were closed questionnaires and mathematical tests. The data analysis technique uses inferential statistical techniques consisting of normality test, linearity test, multicollinearity test and hypothesis testing using linear regression analysis. Based on the results of data analysis, mathematical anxiety shows a moderate criterion of 60%, an average of 44.3 and a standard deviation of 8.05; mathematics learning habits show moderate criteria at 45%, an average of 92.9, and a standard deviation of 140.96; Critical thinking skills of students showed moderate criteria at 55%, an average of 5.45, and a standard deviation of 1.218. In addition, the results of data analysis show that there is an influence of anxiety and study habits of mathematics together on students' critical thinking skills. The amount of influence that is equal to 15.60% with the contribution of the influence of mathematics anxiety of 13.20% and learning habits of mathematics by 5.90%. Then the multiple linear regression equation, i.e. = 16,998 – 0,042.X1 – 0,014.X2.